A case study of incubation of tourism activities in the region of Subotica as a chance of tourism management - Zedi Ildiko; Hnis Lanji Izabel (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
The development of tourism at the micro level can be channeled through various aspects of the implementation of business ideas. One of the features of modern mechanisms is the use of business incubators and their ability to implement business ideas of tourist industry. Specific target groups, who want to do business in the field of tourism, with the support of the incubator can get through the first 3 years of operations, which are needed to stabilize. Incubation of tourism services, so far hasn't been the subject of the research and study in our region, because the incubators were big news in our country. The micro-entrepreneurship, in the sector in which has a lot of beginners in the field of tourism, the problems of management and its development are closely related to the usual problems of starting his own business, with the risks that are specific to the tourism sector. The tourism sector is a very sensitive sector of the economy, who right now, very quickly respond to any changes in the environment. This paper discusses about the possibility of using business incubators for incubation of tourist services, the conditions for the development of management skills, to overcome the risk in the business, the link of business incubation of micro level with the development of the tourism industry, through case studies. The aim is to conclude as specified instructions that will help Micro-entrepreneurs in the process of incubation of tourist services and developing their own organizational management in practice. They will apply normative methods, namely: observation, comparison, analysis and synthesis, inference of induction and deduction.